2020
DOI: 10.1177/2332649220940346
|View full text |Cite
|
Sign up to set email alerts
|

The Role of Skin Color in Latino Social Networks: Color Homophily in Sending and Receiving Societies

Abstract: How does skin color shape the social networks and integration pathways of phenotypically diverse immigrant groups? Focusing on Dominicans and Puerto Ricans, groups with considerable diversity across the Black-White color line, the authors explore whether migrants to the United States have greater color homophily in their primary social networks than nonmigrants in the sending societies. The authors analyze egocentric network data, including unique skin color measures for both 114 respondents and 1,702 alters. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 42 publications
(50 reference statements)
0
1
0
Order By: Relevance
“…11 Among nationally heterogenous Latino subgroups, race and skin color play an important role in friendship formation, with the sending society having a stronger influence on preference than US culture. 47 This suggests that cultural and societal racial views from Latinos' country of origin may affect the formation of Latino friendships in the United States, which will then influence the type of information shared between mixed-race Latino friendship dyads. In addition, we found that LMSM have a higher likelihood of having PrEP-related conversations and encouraging friends to use PrEP when their friends live further from them.…”
Section: Discussionmentioning
confidence: 99%
“…11 Among nationally heterogenous Latino subgroups, race and skin color play an important role in friendship formation, with the sending society having a stronger influence on preference than US culture. 47 This suggests that cultural and societal racial views from Latinos' country of origin may affect the formation of Latino friendships in the United States, which will then influence the type of information shared between mixed-race Latino friendship dyads. In addition, we found that LMSM have a higher likelihood of having PrEP-related conversations and encouraging friends to use PrEP when their friends live further from them.…”
Section: Discussionmentioning
confidence: 99%